Metformin-Associated Lactic Acidosis following Intentional Overdose Successfully Treated with Tris-Hydroxymethyl Aminomethane and Renal Replacement Therapy - Ngan Lam; Gurbir Sekhon; Andrew A. House (Case Reports in Nephrology)
A 43-year-old woman was brought to the hospital with severe metabolic acidosis (pH 6.56, bicarbonate 3 mmol/L, and lactate 18.4 mmol/L) and a serum creatinine of 162 μmol/L with a serum potassium of 7.8 mmol/L. A delayed diagnosis of metformin-associated lactic acidosis was made, and she was treated with tris-hydroxymethyl aminomethane (THAM) and renal replacement therapy (RRT). Following a complete recovery, she admitted to ingesting 180 tablets (90 grams) of metformin. Her peak serum metformin concentration was 170 μg/mL (therapeutic range 1-2 μg/mL). Our case demonstrates an intentional metformin overdose resulting in lactic acidosis in a nondiabetic patient who was successfully treated with THAM and RRT.